Cardiovascular Risk, Risk Knowledge, and Related Factors in Patients - Fatma Zengin; Canan Demir Barutcu (Sakarya Üniversitesi Holistik Sağlık Dergisi, 2023)
Objective: The aim of this study was to investigate cardiovascular risk, risk knowledge, and related factors in patients. Method: The descriptive and corelational study was carried out with 340 patients who applied to the state hospital between November 2018 and March 2019 and agreed to participate in the study. Data was collected through face-to-face interviews with the scale of the Cardiovascular Disease Risk Factors Knowledge Level (CARRF-KL) and Systematic Coronary Risk Evaluation (SCORE) Calculator. Results: In the study, it was found that patients were in the middle risk group in terms of cardiovascular risk, and their risk information level was slightly higher than the average. There was no statistically significant relationship between the level of knowledge of patients and the level of cardiovascular risk (r= -.062, p=.256). Conclusion: The study emphasises that initiatives should be developed to increase awareness of cardiovascular disease risks in Turkey and to increase the level of cardiovascular disease risk information available in order to prevent diseases. Preventative strategies can reduce the risk of cardiovascular disease and improve outcomes. Nurses should assess risk knowledge in patients to ensure best outcomes.